6y-3=9y

Simple and best practice solution for 6y-3=9y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-3=9y equation:


Simplifying
6y + -3 = 9y

Reorder the terms:
-3 + 6y = 9y

Solving
-3 + 6y = 9y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9y' to each side of the equation.
-3 + 6y + -9y = 9y + -9y

Combine like terms: 6y + -9y = -3y
-3 + -3y = 9y + -9y

Combine like terms: 9y + -9y = 0
-3 + -3y = 0

Add '3' to each side of the equation.
-3 + 3 + -3y = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -3y = 0 + 3
-3y = 0 + 3

Combine like terms: 0 + 3 = 3
-3y = 3

Divide each side by '-3'.
y = -1

Simplifying
y = -1

See similar equations:

| 5(P-8)=P+3 | | -8(x+6)=6v-34 | | (-5/6)(x-7) | | w-69=-63 | | 4x+80=50x-12 | | 7=32+b | | -19-6k=6(1+3k) | | 2,3f+12=40 | | 6x^9/x^2 | | 17x-3=9x+13 | | 49x^2-56+16= | | 3t^2-24t+45=0 | | 4p+12= | | (N+4)*3=36 | | 6x+2=3x+7 | | A/6-1=7 | | 11=r/13 | | x/5=4/16 | | 2x+6=3x-9 | | 3x+5=55-9x | | 3x-6.8=31 | | 7d-12=38 | | 125-6x=30x+21 | | 8x^2=5x+7 | | 3/4=9/x-7 | | -2-z=4.5 | | (6-x)/(x-2)-(5x-7)/(2-x) | | 6=-8x-2 | | 114-10x=9x+19 | | 752.6-78.85= | | x+1/6=x-1/x | | 6x-5=7x+5 |

Equations solver categories